Arts and design 2200 & 3200 : a teaching guide - Newfoundland and Labrador. Department of Education. Division of Program Development (Government of Newfoundland and Labrador, Department of Education, Division of Program Development, 1991)
Arts and Design 2200 & 3200 A Teaching Guide